2019
DOI: 10.1136/bmjopen-2018-026336
|View full text |Cite
|
Sign up to set email alerts
|

Fertility rates and the postponement of first births: a descriptive study with Finnish population data

Abstract: ObjectivesWe described the trend of fertility rates, age-specific fertility rates and associated factors in Finland over a 30-year period.DesignA descriptive population-based register study.SettingFertility data, including age at first birth, childlessness and educational levels were gathered from the Finnish Medical Birth Register and Statistics Finland.ParticipantsAll 1 792 792 live births from 1987 to 2016 in Finland.Main outcome measuresCompleted fertility rate, total fertility rate and age-specific fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Cohort fertility is still fairly close to replacement level in Finland, although at a slightly lower level than in the rest of the Nordic countries, due to high rates of continued childbearing among mothers (Eurostat 2019;Jalovaara et al 2019). Cohort fertility is highest for women who start their childbearing at an early age and decreases with increasing age at first birth (Roustaei et al 2019). In Finland, it has declined slightly among the most recent cohorts: among women born in the 1960s, the CFR fell from nearly 2.0 to 1.9.…”
Section: Fertility In Finland Compared With Other Highincome Countriesmentioning
confidence: 98%
“…Cohort fertility is still fairly close to replacement level in Finland, although at a slightly lower level than in the rest of the Nordic countries, due to high rates of continued childbearing among mothers (Eurostat 2019;Jalovaara et al 2019). Cohort fertility is highest for women who start their childbearing at an early age and decreases with increasing age at first birth (Roustaei et al 2019). In Finland, it has declined slightly among the most recent cohorts: among women born in the 1960s, the CFR fell from nearly 2.0 to 1.9.…”
Section: Fertility In Finland Compared With Other Highincome Countriesmentioning
confidence: 98%
“…Previously, it was reported that in the age group of 30e39 years invasive GAS emm28 infections were strongly associated with women (80%, p < 0.001) [7]. In Finland the fertility rate for women in the 20-to 40-year age group is substantially higher than for younger and older age groups [18].…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, around three-quarters of the decline in fertility in the 2010s can be attributed to women having fewer first children (Hellstrand, Nisén and Myrskylä 2020;Roustaei et al 2019). This trend may be partly explained by the postponement 4 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 of the first birth until higher ages.…”
Section: Falling Fertility In the Nordic Countriesmentioning
confidence: 99%